2011
DOI: 10.5830/cvja-2010-072
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome and congenital heart disease : why the regional difference as observed in the Libyan experience?

Abstract: BackgroundChildren with Down syndrome (DS) have about a 40 to 50% incidence of congenital heart disease (CHD). The objectives of this study were to evaluate the distribution and frequency of CHD patterns in Libyan children with DS.MethodsAll patients with DS who were referred to the cardiology clinic between January 1995 and December 2008 were reviewed.ResultsOf the 1 193 patients reviewed, 537 (45%) had an associated CHD. Overall there were 349 (65%) patients who had a single cardiac lesion, and 188 (35%) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 18 publications
(24 reference statements)
9
38
2
1
Order By: Relevance
“…The present study found among 40 CHD patients, 65% had isolated cardiac defect, which is similar to the study in libya, 7 however it is different as compared to 80% in Guatemala, 8 74% in Mexico, 3 78% in Turkey. 11 VSD was the most common isolated defect and was found in 9 of the 40 patients (22.5%), which was followed by AVSD (15%) then ASD (10%) and PDA (10%).…”
Section: Original Article |supporting
confidence: 88%
“…The present study found among 40 CHD patients, 65% had isolated cardiac defect, which is similar to the study in libya, 7 however it is different as compared to 80% in Guatemala, 8 74% in Mexico, 3 78% in Turkey. 11 VSD was the most common isolated defect and was found in 9 of the 40 patients (22.5%), which was followed by AVSD (15%) then ASD (10%) and PDA (10%).…”
Section: Original Article |supporting
confidence: 88%
“…However,regional proximity alone cannot explain all the differences, as studies in African countries that also have regional proximity with Europe, such as Libya, have exhibited results that globally encompassed the spectrum of CHD in DS seen in Europe but with quite different rates in the different CHDs 21. As illustrated by the differences in reported rates of the different CHDs inDS between countries in close proximity, such as the USA and Mexico or other Latin American countries,3,4,8,11 it appears that regional proximity may have a greater effect in cases of geographical areas with long-standing populations, as in the Mediterranean area.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8][9][10][11][12][13][14][15][16][17] The types of heart defect may vary according to geographic region. In this study, the most common type was atrial septal defect, which was similar to the findings from other Table 1.…”
Section: Discussionmentioning
confidence: 99%